2016
DOI: 10.1242/dmm.022848
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous shaker rat mutant – a new model for X-linked tremor/ataxia

Abstract: The shaker rat is an X-linked recessive spontaneous model of progressive Purkinje cell (PC) degeneration exhibiting a shaking ataxia and wide stance. Generation of Wistar Furth (WF)/Brown Norwegian (BN) F1 hybrids and genetic mapping of F2 sib-sib offspring using polymorphic markers narrowed the candidate gene region to 26 Mbp denoted by the last recombinant genetic marker DXRat21 at 133 Mbp to qter (the end of the long arm). In the WF background, the shaker mutation has complete penetrance, results in a stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 51 publications
1
21
2
Order By: Relevance
“…Four rats exhibited tremor at 9 to 11 weeks of age, the last 2 having symptom onset at 14 and 19 weeks. These were consistent with previous qualitative determinations that shaker rats first display symptoms between 9 and 20 weeks of age . Whereas qualitative observations noted onset no earlier than 9 weeks, we quantitatively found that shaker rats demonstrated significantly more tremor than WT animals ( bca , p < 0.00001) at all ages from 8 weeks on.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Four rats exhibited tremor at 9 to 11 weeks of age, the last 2 having symptom onset at 14 and 19 weeks. These were consistent with previous qualitative determinations that shaker rats first display symptoms between 9 and 20 weeks of age . Whereas qualitative observations noted onset no earlier than 9 weeks, we quantitatively found that shaker rats demonstrated significantly more tremor than WT animals ( bca , p < 0.00001) at all ages from 8 weeks on.…”
Section: Resultssupporting
confidence: 92%
“…These were consistent with previous qualitative determinations that shaker rats first display symptoms between 9 and 20 weeks of age. 18 Whereas qualitative observations noted onset no earlier than 9 weeks, we quantitatively found that shaker rats demonstrated significantly more tremor than WT animals (bca, p < 0.00001) at all ages from 8 weeks on. Power spectra of representative 10-week shaker and WT rats are shown (see Fig 2A), along with tremor versus age (see Fig 2B).…”
Section: Model Characterizationcontrasting
confidence: 58%
See 3 more Smart Citations